EVALUATAION OF DIMENSION ANALYSIS THROUGH “MANGKANG ZOO TOURIST ATTRACTION” PROMOTION PROGRAM IN SEMARANG CITY, CENTRAL JAVA, INDONESIA - Ningsih, Tri Yuni; Suwitri, Sri; Susilowati, Etty; ., Kismartini (Advances in Social Sciences Research Journal, 2018)
Mangkang zoo in Semarang city is hopes to become tourist attraction and able to increase tourist amount both of local or foreign because of the strategic location, space between one coral to another is too close, and children playground completely. But there are still weakness such as this zoo management hasn’t done maximally and impact to the lack of tourist visitation. This research aims to evaluate implementation promotion development program of Mangkang zoo in Semarang city based on Input dimension, Process, Output and Outcome. Relating to this problem, it is needed societies participation through their role as tourism development object, so that they role will determine successful program of marketing development/ promotion activity. This research uses descriptive qualitative because it explains phenomenon descriptively without determining phenomenon appearing quantity, but the deep information in every phenomenon. This research focuses into evaluation program of Mangkang zoo tourism promotion program in Semarang city. Technique of data collecting is done by Triangulation through deep interview activity with many informants, questionnaire, and documentation. The lack of tourist visiting and tourism stakeholder also the raising local income relating to tourist retribution is one of indication of development program into tourism promotion that is done by Cultural and Tourism Institution in Semarang city hasn’t done optimally.